Vestibular neuritis after COVID-19 vaccination - Junhui Jeong (Taylor & Francis Group, 2021)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 and presents with pneumonia as the most frequent and serious manifestation. COVID-19 vaccination is an important and urgent interest globally due to COVID-19's rapid spread and high rates of mortality and morbidity. Vestibular neuritis (VN) is an acute vestibular syndrome that causes acute and spontaneous vertigo due to unilateral vestibular deafferentiation, leading to nausea or vomiting and unsteadiness that can last from days to weeks. Reactivation of latent type 1 herpes simplex virus, autoimmune disorders, and microvascular ischemia are hypothesized to be etiologies. Herein, the case of a 54-year-old man who developed VN within three days after COVID-19 vaccination is presented. There have been no reports of VN after vaccination for COVID-19 or other viral diseases. Although the association between VN and COVID-19 vaccination remains unclear, clinicians should be aware that VN may occur as an adverse event of COVID-19 vaccination.